Tissue Flossing Around the Thigh Does Not Provide Acute Enhancement of Neuromuscular Function - Paravlic, Armin H.; Segula, Jure; Drole, Kristina; Hadzic, Vedran; Pajek, Maja; Vodicar, Janez (Frontiers in Physiology, 2022)
Nowadays, various methods are used for acute performance enhancement. The most recent of these is tissue flossing, which is becoming increasingly popular for both performance enhancement and rehabilitation. However, the effects of flossing on athletic performance have not been clearly demonstrated, which could be due to differences in the methodology used. In particular, the rest periods between the end of the preconditioning activity and the performance of the criterion task or assessment tools varied considerably in the published literature. Therefore, the present study aimed to investigate the effects of applying tissue flossing to the thigh on bilateral countermovement jump performance and contractile properties of vastus lateralis (VL) muscle. Nineteen recreational athletes (11 males; aged 23.1 ± 2.7 years) were randomly assigned to days of flossing application (3 sets for 2 min of flossing with 2 min rest between sets) with preset experimental pressure (EXP = 95 ± 17.4 mmHg) or control condition (CON = 18.9 ± 3.5 mmHg). The first part of the measurements was performed before and after warm-up consisting of 5 minutes of cycling followed by dynamic stretching and specific jumping exercises, while the second part consisted of six measurement points after flossing application (0.5min, 3min, 6min, 9min, 12min, 15min). The warm-up improved muscle response time (VL=-5%), contraction time (VL=-3.6%) muscle stiffness (VL=17.5%), contraction velocity (VL=23.5%), jump height (13.9%) and average power (10.5%). On the contrary, sustain time, half-relaxation time and take-off velocity stayed unaltered. Flossing, however, showed negative effects for muscle response time (F=18.547, p < 0.001), contraction time (F=14.899, p<0.001), muscle stiffness (F=8.365, p < 0.001), contraction velocity (F=11.180, p < 0.001), jump height (F=14.888, p < 0.001) and average power (F=13.488, p < 0.001), whereas sustain time, half-relaxation time and take-off velocity were unaffected until the end of the study protocol regardless of condition assigned and/or time points of assessment. It was found that the warm-up routine potentiated neuromuscular function, whereas the flossing protocol used in the current study resulted in fatigue rather than potentiation. Therefore, future studies aimed to investigate the dose-response relationship of different configurations of preconditioning activities on neuromuscular function are warranted.